Examination on Philosophy-Based Management of Contemporary Japanese Corporations: Philosophy, Value Orientation and Performance - Wang, Yingyan (Journal of business ethics, 2009)
Despite the recognition of the importance of philosophy-based management in recent Japanese management practices, there has been little effort to systematically examine this topic from a normative view. With a sample of 152 electrical machinery companies, this study attempts to identify the underlying value orientations incorporated in the normative statement of corporate management philosophy and furthermore examines the complex relationships between corporate value orientations and various performance indexes. The article shows that although the adoption of a corporate management philosophy does not contribute to corporate financial performance directly, some value orientations might contribute to non-financial performance and long-term performance potentials. Especially, CSR environmental performance might be contributed by customer orientation and harmony; human resource management performance is associated with partner orientation and harmony; growth potential might be related with global orientation, entrepreneurship, and honesty. Furthermore, the negative relationship between increase of sales effort and CSR environmental performance also implies that it deserves careful consideration and attention for a company to balance the interests of various stakeholders.